What are the needs in oral antitumor therapy? An analysis of patients’ and practitioners’ preferences - Hester, Anna; Henze, Franziska; Debes, Anna Marie; Schubert, Charlotte Leonie; Koenig, Alexander; Harbeck, Nadia; Wuerstlein, Rachel (Frontiers in Oncology, 2024)
Background: Since the European approval of CDK4/6-inhibitors in 2016, the treatment of patients with hormone-receptor-positive, HER2-negative metastatic breast cancer has changed significantly. Compared to chemotherapy, endocrine-based therapy has different treatment regimens and is associated with new side effects. Oral therapy aims for optimal drug efficacy and long treatment times while maintaining maximum independence and quality of life resulting in conservation of medical staff resources. Methods: A monocentric analysis of therapy preferences of practitioners (25 nurses and physicians) and patients (11 on endocrine monotherapy, 17 on endocrine-based therapy and 14 on intravenous chemotherapy) was performed using specific questionnaires. Preferences were assesed using a four-point Likert scale or bidirectional response options. Results: All patients were highly supportive of oral therapy (mean agreement score on Likert scale 1.3, p<0.001 vs. all other options) and a consultation interval of 4 weeks (2.0, p=0.015 vs. 3 weeks). Practitioners also preferred oral therapy (1.4) and visits every 4 weeks (1.6). In general, patients on oral therapies reported higher compatibility of their therapy with daily life than patients on chemotherapy (1.6 and 1.7 vs. 2.6, p=0.006). Outpatient oncology is the main source of information for all patients, mainly in case of side effects (2.0) and open questions (1.8). Regarding oral anti-tumor therapy regimens, patients do not show a significant preference for a specific regimen, while practitioners prefer a continuous regimen (1.6) over a 21/7-regimen (21 days on and 7 days off therapy, 2.5) . Patients are likely to accept mild side effects (e.g. neutropenia, diarrhea, polyneuropathy, fatigue) and would still adhere to their initial choice of regimen (continuous or 21/7). Only when side effects occur with a severity of CTCAE grade 3 do patients prefer the regimen in which the side effects occur for a shorter period of time. Conclusion: Patients and practitioners prefer oral anti-tumor therapy – both continuous and 21/7 regimens - over other application forms. Patient education and proper therapy management, supported by additional tools, contribute to specific management of side effects and high adherence. This allows quality of life to be maintained during long-term therapy with CDK4/6-inhibitors in patients with metastatic breast cancer.